Effects of 8 weeks equal-volume resistance training with different workout frequency on maximal strength, endurance and body composition - Arazi, H.; Asadi, A. (International Journal of Sports Science and Engineering, 2011)
The purpose of this study was to determine the effects of short-term equal-volume resistance training with different workout frequency on maximal strength, endurance, and body composition in novice subjects. Thirty-nine healthy males comprised four groups; total-body resistance training (12 exercises for one session per week) (part I=10), total-body resistance training (12 exercises for two sessions per week) (part II=10), lower-body, upper-body, and upper-body resistance training (12 exercises for three sessions per week) (part III=9), and control group (CG=10). Assessments of body composition, leg and arm circumferences, body weight, strength (one repetition maximum in bench and leg press) and endurance (bench and leg press) were determined before and after 8 weeks of training. One repetition maximum in bench and leg press was improved significantly in all training groups (P < 0.05). All groups increased body weight, body composition, and bench and leg press endurance (P < 0.05), but PIII group showed a little improvement rather than other groups (P > 0.05). The PIII group not only increased thigh circumference but also improved arm circumference, whereas the PI and PII groups changed either arm circumference or thigh circumference (P < 0.05). It is concluded that in healthy young men, whole and split weight training routine produce similar results over the first 2 months of training, with minimal differences among groups.